Commissureless endocytosis is correlated with initiation of neuromuscular synaptogenesis. - Wolf, B.; Seeger, M.A.; Chiba, A. (Development, 1998)
We show that the Commissureless (COMM) transmembrane protein is required at neuromuscular synaptogenesis. All muscles in the Drosophila embryo express COMM during the period of motoneuron-muscle interaction. It is endocytosed into muscles before synaptogenesis. In comm loss-of-function mutants, motoneuron growth cones fail to initiate synaptogenesis at target muscles. This stall phenotype is rescued by supplying wild-type COMM to the muscles. Cytoplasmically truncated COMM protein fails to internalize. Expressing this mutant protein in muscles phenocopies the synaptogenesis defects of comm mutants. Thus, synaptogenesis initiation is positively correlated with endocytosis of COMM in postsynaptic muscle cells. We propose that COMM is an essential part of the dynamic cell surface remodeling needed by postsynaptic cells in coordinating synaptogenesis initiation.